Fortalecimiento de la capacitación docente para la atención inclusiva de estudiantes con necesidades educativas especiales - Chipantiza Guato, Karen Thalía (2025)
This research addresses the strengthening of teacher training as a key strategy to improve the inclusive care of students with special educational needs (SEN) in the current educational context. Despite international and national normative advances in inclusion, significant gaps persist in teacher training, limiting the implementation of effective inclusive pedagogical practices. The general objective of the study was to analyze how teacher training affects the quality of care for students with SEN, considering its impact on equity, participation, and educational achievement. To this end, a theoretical review and contextual analysis of the Ecuadorian education system were carried out, showing that many teachers do not have the appropriate preparation or the necessary institutional support. It is concluded that continuous, contextualized and diversity-focused teacher training is essential to build inclusive educational environments. It is also recommended to implement comprehensive training programs, promote interdisciplinary work, and generate sustainable public policies that guarantee the right to quality education for all students, especially for those with SEN.